Étude palynologique du site de Montbaron (Indre) - Bui Thi Mai; Michel Girard (Archéologie Médiévale)
The Iron Age landscape around Montbaron is characterised by a vegetation pattern in which some trees of the mainly destroyed sub boreal forest have survived, by the persistence of riverine vegetation and by cereal and buckwheat growing. The Medieval environment is more open than during the preceding phase : only thickets and hedges seem to subsist, and the riverine vegetation has been considerably diminished. The presence of buckwheat pollen during the Iron Age constitutes a new element for understanding the cultivation of this taxon in Western Europe, and the existence of a high level of cruciferous pollen of the Sinapsis type (mustard, rape…) and Umbelliferae confirms the practice of varied crops by the farmers of the 11th and 12th centuries.